SLOPE PROFILE MORPHOMETRY AS AN INDICATOR FOR SLOPE MOVEMENT (Journal of Sciences, Islamic Republic of Iran)
Two dimensional slope profile morphometric investigation in a part of the land failure prone Garhwal region of the Lesser Himalaya, Tehri district, U. P., India, indicates that the landslip morphology is closely related to the dominant movement processes active in this terrain. Technique developed for the morphometric analysis of landslips involves the use of five morphometric indices. Each index has been formulated to give an indication of the processes responsible for producing variation on landslip form. The measurements indicated the degree of dilation, flowage, displacement and tenuity. The depth/length ratio is used as a numerical parameter to classify landslips into process groups. Multivariate discriminant function criteria have been worked out to differentiate between various slope movement processes. The result indicated that among all two dimensional slope profile morphometric indices, Classification, Dilation and Tenuity indices contribute significantly in discriminating various slope movement processes. Based on these indices, bivariate and univariate plots have been prepared as discriminant tools to predict various types of slope movements.